REVIEW OF EMPLOYEE'S WORK MOTIVATION AT ARBORBIZ MAKASSAR HOTEL - Indriati Amirullah; Nurasia Natsir; Natsir Mallawi; Syafaruddin Syafaruddin; Nurasia Natsir (Proceeding of The International Conference on Economics and Business, 2022)
The aim of this research is to find out the review of employee motivation at the Hotel Arborbiz Makassar.The type of research used is descriptive qualitative, in which the author describes the results of observations and direct interviews with employees at Hotel Arborbiz Makassar. Writing this Final Project is the result of research conducted from June to July 2022.The results showed that the work motivation of employees at Hotel Arborbiz Makassar was seen from several factors that influenced employee motivation, such as promotions, work performance, the work itself, awards, responsibilities and recognition from superiors.